Controlling in the management of the Insurance Company - Misheva, Irena (Research Papers, 2014)
This survey deals with questions concerning the application of controlling in insurance. The emphasis is on the specific characteristics of strategic and effective controlling as elements of insurance management. The attention is drawn to their basic tools and their significance for the insurance practice. Examines are the ABC-analysis and analysis of the costs of business processes in the insurance company. The survey presents the potentialities of the financial results analysis of insurance and the analysis of the competitiveness of the insurance company.In the introduction the aims, the thesis, the object and the tasks of the survey are formulated.The main part of the survey emphasizes on the positioning of "Controlling" in the structure of the company. This part presents the connection of controlling with the other types of management in the structure of the insurance company. The research outlines the role of controlling in the realization of insurance business processes. The survey reveals some impeding factors in the application of controlling in insurance and specifies some methods for overcoming them.In thefinal part the author makes the conclusion that the potentialities of controlling will provoke the insurers to use its tools in the future to increase the effectiveness of insurance. Controlling has become a philosophy related to the strategic thinking of the managers of insurance companies, aiming at stable and successful development of insurance business in the future.